Pemanfaatan Aplikasi Microsoft Word Bagi PKBM Bina Bangsa Tangerang - Ratna Kusumawardani (Jurnal Pengabdian kepada Masyarakat TEKNO (JAM-TEKNO), 2025)
The success of the learning process in an educational institution or institution will certainly never be separated from the role of technology which is currently developing very rapidly so that all scientific fields must be able to keep up with the changing times. As one example in the world of education, where it has now followed the development of the times by utilizing technology, such as the implementation of learning using computers or laptops. Education will produce quality human resources if balanced with the role of technology so that these human resources can face the challenges of life that are increasingly advanced and have the proactive ability to be able to adapt to the changing times. This is the basic capital of development to fulfill this, the lecturers of Budi Luhur University in collaboration with PKBM Bina Bangsa Tangerang to hold computer training using Microsoft Office applications, one of which is Microsoft Word as an effort to provide soft skills and improve abilities to produce quality human resources. This training applies scientific methods to make learning more active and not boring by means of practical work in the Budi Luhur University computer laboratory involving 30 students. Based on the processed questionnaire data, it shows that those who understand the training material are 92% so it can be recognized that this training is running well. It is hoped that the results of this activity can increase the skills of students to apply for jobs after graduating from school.